The economics of clusters lessons from the French experience - Duranton, Gilles (Oxford : Oxford University Press, 2010)
Clusters policies have become a key focus for policy makers in recent years. This book looks at the development of clusters of economic activity and their importance in shaping industrial and public policy. It examines the success and failures of policy in France and extrapolates its findings to the rest of the world.
Description based on print version record.
Includes bibliographical references.
Keywords: Industrial clusters; Industrial clusters -- Government policy -- France